1995
DOI: 10.1074/jbc.270.20.11977
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Second Region Upstream of the Mouse Heme Oxygenase-1 Gene That Functions as a Basal Level and Inducer-dependent Transcription Enhancer

Abstract: A 161-base pair fragment (AB1) approximately 10 kilobase pairs upstream of the transcription start site of the mouse heme oxygenase-1 gene functions as a basal level and inducer-dependent enhancer. AB1/chloramphenicol acetyltransferase fusion genes stably transfected into mouse hepatoma (Hepa) cells or L929 fibroblasts were activated 7-8- or 17-22-fold, respectively, after treatment of the cells with either CdCl2 or heme. The AB1 fragment is composed largely of three tandem repeats containing two conserved cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(131 citation statements)
references
References 30 publications
3
127
1
Order By: Relevance
“…Further, Alum et al(1995) have shown HO-1 gene to be induced by reactive oxygen species like H 2 O 2 and singlet oxygen ( 1 O 2 ) which set the reduction reaction leading to enhanced bilirubin content. It is known that both biliverdin and bilirubin exhibit antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Alum et al(1995) have shown HO-1 gene to be induced by reactive oxygen species like H 2 O 2 and singlet oxygen ( 1 O 2 ) which set the reduction reaction leading to enhanced bilirubin content. It is known that both biliverdin and bilirubin exhibit antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Here we determined the ability of TGF-␤ 1 to activate the transcription of an ho-1 promoter/luciferase reporter fusion gene containing the 33-bp HO-1 minimal promoter sequences and the 268-bp HO-1 enhancer SX2, previously identified as a mediator of ho-1 gene activation by a variety of stimuli in A549 cells (2,3). Furthermore, in A549 cells, treatment with actinomycin D, which inhibits transcription, attenuated the ability of TGF-␤ 1 to induce HO-1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The p38 MAPK pathway was blocked either by the selective chemical inhibition of p38 MAPK with SB-203580 or by genetic blockade with a dominant-negative mutant of p38 MAPK. HO-1 promoter activity was assessed by transfection of a luciferase reporter construct (pMHO1luc-33ϩSX2) containing the 33-bp HO-1 minimal promoter sequences and the 268-bp HO-1 enhancer SX2, previously identified as a mediator of ho-1 gene activation by a variety of stimuli (2,3). As shown in Fig.…”
Section: Inhibition Of the P38 Mapk Pathway Downregulates Tgf-␤ 1 -Inmentioning
confidence: 99%
“…Concerning regulatory mechanism for stress protein induction, a cDNA for a novel serine/threonine kinase, Ern lp, has been recently isolated from yeast, and this kinase was shown to be essential for a set of specific stress gene expression induced by perturbation of nascent protein synthesis [25,26]. The A 12-PGJ 2-induced HSP70 gene expression has been shown to require de novo protein synthesis [22,23]. The A12-PGJ2-induced HO-I gene expression also required de novo protein synthesis (data not shown).…”
Section: Vl Negishi Et Al/febs Letters 372 (1995) 279 282mentioning
confidence: 99%